2009
DOI: 10.1161/circresaha.109.197533
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the SDF-1/CXCR4 Axis Attenuates Neonatal Hypoxia-Induced Pulmonary Hypertension

Abstract: Abstract-Exposure of the neonatal lung to chronic hypoxia produces significant pulmonary vascular remodeling, right ventricular hypertrophy, and decreased lung alveolarization. Given recent data suggesting that stem cells could contribute to pulmonary vascular remodeling and right ventricular hypertrophy, we tested the hypothesis that blockade of SDF-1 (stromal cell-derived factor 1), a key stem cell mobilizer or its receptor, CXCR4 (CXC chemokine receptor 4), would attenuate and reverse hypoxia-induced cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
85
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 45 publications
10
85
1
Order By: Relevance
“…This finding is in keeping with our previous study showing that antagonism of SDF-1 or its other receptor, CXCR4, could attenuate PH in neonatal mice (10). This is also consistent with the observations of Gambaryan et al (13), who demonstrated that the CXCR4 antagonist AMD3100 inhibited hypoxia-induced pulmonary vascular remodeling in an adult model and showed synergistic effects when combined with a CXCR7 antagonist.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This finding is in keeping with our previous study showing that antagonism of SDF-1 or its other receptor, CXCR4, could attenuate PH in neonatal mice (10). This is also consistent with the observations of Gambaryan et al (13), who demonstrated that the CXCR4 antagonist AMD3100 inhibited hypoxia-induced pulmonary vascular remodeling in an adult model and showed synergistic effects when combined with a CXCR7 antagonist.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in keeping with other studies showing that chemokines may potentiate vascular remodeling by modulating pulmonary vascular cell proliferation (10,(37)(38)(39). Moreover, CXCR7 has been specifically shown to increase the proliferation of lung microvascular endothelial cells and several tumor lines (12,15,17).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations